The implementation of peer assessment in product performance assessment in project-based learning on ecosystem materials - Yanti Hamdiyati; Ilham Nur Iman Maulana; Siti Sriyati (Universitas Ahmad Dahlan, 2021)
The teacher's difficulty in assessing student performance when students work in groups outside class hours causes the need for peer assessment to be carried out. Project-based learning is a suitable space for applying peer assessment because it consists of tasks that students in groups usually do. This study describes the application of peer assessment in product performance assessment in project-based learning on ecosystem materials. This study uses a descriptive method involving 34 high school students in class X. Peer assessment is done by students assessing the products made by their group of friends. The application of peer assessment in this study was carried out three times, namely at the stage of product design, product assessment, and product presentation. An analysis of the performance assessment results through peer assessment is conducted, and the similarity of the results of the peer assessment to the teacher's assessment at each stage. The study results showed that there was a tendency for an increasing student's ability to judge. This result is evidenced by the increasing similarity of teacher assessments and peer assessments at each stage. The similarity between peer assessment and teacher assessment at the product design stage is 58.8%; product assessment stage by 64.7%; and the product presentation stage of 70.6%. The student response questionnaire identified that the application of peer assessment provided many benefits to students. Based on the results of this study, peer assessment can be an alternative in overcoming teachers' difficulties in assessing student performance when project work is carried out outside class hours through project-based learning.